The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/jacs.9b13757
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing the Hydrodefluorination of CF3-Substituted Alkenes by PhSiH3. H• Transfer from a Nickel Hydride

Abstract: The hydrodefluorination of CF 3-substituted alkenes can be catalyzed by a nickel(II) hydride bearing a pincer ligand. The catalyst loading can be as low as 1 mol%. gem-Difluoroalkenes containing a number of functional groups can be formed in good to excellent yields by a radical mechanism initiated by H • transfer from the nickel hydride. The relative reactivity of various substrates supports the proposed mechanism, as does a TEMPO trapping experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 83 publications
0
46
1
Order By: Relevance
“…For example, the Norton group has recently found that Gade's iso-PmBox nickel hydride can undergo MHAT with trifluoromethylstyrenes. 46 Since WF MHAT (Mn–H and Fe–H) itself can be merged with canonical nickel cross-coupling via bimetallic dual catalysis, 47 reactivity of the iso-PmBox nickel hydride hints at the possibility of a dual-functional, but mono-metallic catalytic cycle.…”
Section: Metal Hydrides In Mhat Reactionsmentioning
confidence: 99%
“…For example, the Norton group has recently found that Gade's iso-PmBox nickel hydride can undergo MHAT with trifluoromethylstyrenes. 46 Since WF MHAT (Mn–H and Fe–H) itself can be merged with canonical nickel cross-coupling via bimetallic dual catalysis, 47 reactivity of the iso-PmBox nickel hydride hints at the possibility of a dual-functional, but mono-metallic catalytic cycle.…”
Section: Metal Hydrides In Mhat Reactionsmentioning
confidence: 99%
“…All rights reserved. 8, 142.6, 136.0, 134.5, 133.9, 133.3, 131.9, 129.7, 128.9, 126.3, 125.0, 118.6, 111.3, 80.7, 20.6, 20.5 2,142.0,136.1,134.5,133.9,133.4,129.8,129.6,129.0 (t,J = 32.03 Hz),128.8,126.3 5, 159.9, 141.9, 135.6, 135.2, 134.9, 132.2, 130.7, 129.8, 129.6, 129.5, 128.0, 127.2, 126.5, 88.8, 52.2, 21.0, 20. 9, 147.1, 139.1, 135.8, 134.8, 134.6, 134.0, 133.2, 129.8, 129.6, 125.1, 123.7, 122.8, 81.2, 20.6, 20.5 (s, 3H), 2.25 (s, 3H). 13 C NMR (125 MHz, DMSO-d6) δ 192.9, 163.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[1] Therefore, much attention has been paid to the the preparation of functionalized gem-dialkenes. For example, Norton [2] reported a method for synthesis of gem-difluoroalkenes via the nickel-hydride-catalyzed hydrodefluorination of CF3 alkenes (Scheme 1A, path i). The rhodium-catalyzed desulfanylative gem-diborylation of 2-arylvinyl sulfides for synthesis of (2,2-diborylvinyl)arenes were also reported (Scheme 1A, path ii) [3] .…”
mentioning
confidence: 99%
“…Norton and co-workers demonstrated the hydrodefluorination reactions of CF 3 -substitited alkenes catalyzed by Ni(II)-hydride complexes. The reaction was mediated by H-atom transfer from Ni(II)-hydride, followed by defluorination 35 .…”
Section: Introductionmentioning
confidence: 99%